Single-cell transcriptome analysis identifies neutrophil-related prognostic signatures in hepatocellular carcinoma - Yang, Shuting; Wang, Dan; Du, Jinghui (Journal of Gastrointestinal Oncology, 2026)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality worldwide, with neutrophils playing complex dual roles in tumor progression and immune regulation. The heterogeneous nature of the tumor immune microenvironment necessitates precise molecular characterization for improved prognostic stratification and therapeutic targeting. This study aimed to develop and validate a neutrophil-related prognostic signature for HCC by integrating single-cell and bulk transcriptomic data, in order to improve prognostic stratification and identify potential therapeutic targets.